Semantic Typicality Effects in Primary Progressive Aphasia. Issue 5 (August 2018) - Riley, Ellyn A.; Barbieri, Elena; Weintraub, Sandra; Mesulam, M. Marsel; Thompson, Cynthia K.
Prototypical items within a semantic category are processed faster than atypical items within the same category. This typicality effect reflects normal representation and processing of semantic categories and when absent may be reflective of lexical–semantic deficits. We examined typicality effects in individuals with semantic and nonsemantic variants of primary progressive aphasia (PPA; semantic—PPA-S, agrammatic—PPA-G), a neurodegenerative disorder characterized by specific decline in language function, and age-matched controls. Using a semantic category verification task, where participants were asked to decide whether visual or auditory words (category typical, atypical, or nonmembers) belonged within a specified superordinate category, we found a typicality effect (ie, faster response times for typical vs atypical items) for all participant groups. However, participants with more severe PPA-S did not show a typicality effect in either modality. Findings may reflect increased intracategory semantic blurring as the disease progresses and semantic impairment becomes more severe.